Simulations of non-stationary frequency content and its importance to seismic assessment of structures. - Wang, Junjie (Earthquake engineering & structural dynamics.)
To verify the importance of the non-stationary frequency characteristic of seismic ground motion, a joint time frequency analysis technique of time signals, called chirplet based signal approximation, is developed to extract the non-stationary frequency information from the recorded data. The chirplet-based signal approximation is clear in concept, similar to Fourier Transform in mathematical expressions but with different base functions. Case studies show that the chirplet based signal approximation can represent the joint time frequency variation of seismic ground motion quite well. Both the random models of uniform modulating process and evolutionary process are employed to generate artificial seismic waves. The joint time frequency modulating function in the random model of evolutionary process is determined by chirplet based signal approximation. Finally, non-linear response analysis of a SODF system and a frame structure is performed based on the generated artificial seismic waves. The results show that the non stationary frequency characteristic of seismic ground motion can significantly change the non-linear response characteristics of structures, particularly when a structure goes into collapse phase under seismic action. It is concluded that non-stationary frequency characteristics of seismic ground motion should be considered for the assessment of seismic capacity of structures.